(untitled) (Research, Society and Development, 2022)
This work is part of still ongoing research developed along GEPETHE - Group of Studies and Research in Theory of History and Education. Its objective is to analyze the relations of interest and investment that permeate Brazilian education and still ponder about how the institutional molds that have established themselves are, as put by Walter Benjamin, monuments of barbarism.. This text is still traversed by the works of theorics of education, like István Mészáros, Dermeval Saviani and Paulo Freire, and researcher in the field of teaching of History and historical education, like Jörn Rüsen, Michel de Certeau, Ana Maria Monteiro and, again, Walter Benjamin. With these authors it is seeked to understand approximations and withdrawals of the more humanistic theories on the teaching of History and education with the guiding documents and base the molds of Brazilian basic education, like the BNCC, the Common Curricular National Basis, and the New Law of Guidelines and Bases, just as its relation with didactic tools, like textbooks and the syllabus of the courses that educate teachers, as to consider the social effects that this bears and rethink the approaches and theories of the teaching of History in the schools through the documents that outline the bases of Brazilian education. It’s still questioned the hierarchy of knowledge and its place of production and it’s also thought of the possibilities of an education against the grain.